Two new glycosidic acids, calyhedic acids E and F, in crude resin glycoside fraction from Calystegia hederacea. Issue 1 (22nd December 2021) - Ono, Masateru; Saito, Nao; Minamishima, Haruna; Yasuda, Shin; Tsuchihashi, Ryota; Okawa, Masafumi; Kinjo, Junei; Miyashita, Hiroyuki; Yoshimitsu, Hitoshi; Nohara, Toshihiro
Abstract: Two new glycosidic acids, calyhedic acids E (1a ) and F (2a ), were isolated from the glycosidic acid fraction afforded by alkaline hydrolysis of the crude resin glycoside fraction obtained from whole plants of Calystegia hederacea Wall. Compounds 1a and 2a were characterised as 11 S -hydroxyhexadecanoic acid 11- O -β-D-glucopyranosyl-(1→6)- O -β-D-glucopyranosyl-(1→6)- O -β-D-glucopyranosyl-(1→3)-[ O -α-L-rhamnopyranosyl-(1→2)]- O -β-D-glucopyranosyl-(1→2)-β-D-quinovopyranoside and an isomer of 1a, in which the 11 S -hydroxyhexadecanoyl residue of 1a was replaced by a 12 S -hydroxyhexadecanoyl residue, respectively, on the basis of spectroscopic data. Graphical Abstract: